Importância da resposta auditiva de estado estável no diagnóstico da surdez em lactentes com risco para a deficiência auditiva: correlações com os achados do potencial evocado auditivo de tronco encefálico - Silva, Daniela Polo Camargo da [UNESP] (2015)
Introduction: The hearing assessment in neonates is currently done by objective tests, such as otoacoustic emissions and the brainstem auditory evoked potential (BAEP), however the main limitation of these assessment methods it is not to provide accurate information on the hearing threshold by specific frequencies, especially in low frequencies. Auditory steady-state response (ASSR) is a complementary technique to the ones existing for the deafness diagnosis in children and its main advantage is to, objectively and automatically predict the hearing thresholds by specific frequency. Objective: To verify if there is concordance between the BAEP and ASSR tests in the infants hearing threshold assessment. Methods: Prospective analytical study. Comprisal criterion: born infants in the study site, with risk indicators for hearing loss and who were submitted to ABR and ASSR tests in the same session. Variants studied: personal data, risks indicators for hearing loss and findings of BAEP and ASSR tests. Comparisons were considered significant for p <0.05. Results: 66 neonates were included, 47% were male (n = 31), median age of 1.2 months, mean gestational age of 31 weeks and mean birth weight 1601g. Thirteen infants had abnormal BAEP (20%), and ten of them had accumulated more than one risk indicator. Higher sensitivity and specificity points in the ASSR for the frequencies of 500, 1000, 2000 and 4000 Hz in the right ear were, respectively, 47.5; 62.5; 42.5 and 37.5 and the left ear 65; 45; 55 and 52.5. Conclusion: There was concordance between the ABR and ASSR tests in infants with risk for hearing loss, being possible to distinguish who have normal hearing from those with hearing loss